Inflammatory biomarkers in cerebral venous thrombosis versus ischemic stroke: a network meta-analysis - Shen, Xinlong; Chen, Ling; Shen, Liling; Chen, Shuling; Mu, Shuwen; Chen, Li; Wang, Shousen; Li, Ziqi (Frontiers in Neurology, 2025)
BackgroundIn cerebrovascular diseases (CVD), the management strategies for ischemic stroke (IS) and cerebral venous thrombosis (CVT) have significant differences, but the underlying inflammation-driven mechanisms in these two conditions have not been fully translated into individualized intervention criteria.MethodsWe searched PubMed, Embase, Web of Science and Cochrane Library through February 1, 2025, and included 18 eligible studies in a Bayesian network meta-analysis following PRISMA-NMA. The data were processed using Revman (version 5.4.1) and R (version 4.3.3). The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) method was used to assess the quality of evidence. This study was registered in PROSPERO (CRD42024539498).ResultsIn total, 18 studies were included in the review. The results showed that acute-phase inflammatory markers were significantly elevated in both CVT and IS. CVT was associated with a relatively stronger systemic inflammatory response, while lymphocyte counts were reduced in both, suggesting a immunosuppressive phenomenon in cerebral thrombotic disease. This network Meta-Analysis showed that CRP (MD = 7.58, 95% CI: 2.48–14.09) and IL-6 (MD = 6.98, 95% CI: 2.75–11.44) were more significantly elevated in the acute phase in CVT patients than in IS patients, suggesting they could serve as key inflammatory markers for differentiating the two conditions.ConclusionInflammatory markers exhibit both specific differences and shared characteristics in CVT and IS. CRP and IL-6 were higher in CVT than in IS in Bayesian NMA, suggesting potential adjunctive markers for differential diagnosis; however, these findings are hypothesis-generating and require prospective validation, and neuroimaging remains the diagnostic gold standard.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024539498, CRD42024539498.